(-4x puterea2)(-3x)+(-4x)(+5x puterea2)-(-2x)(-4x)(-3x)+2x(-8xputerea2) si(-8ab)(-5ab)-(-5a puterea2)(-6b puterea2)+(3a)(-10ab puterea2) ajutor!!!
Răspunsuri la întrebare
Răspuns de
1
(-4x²)(-3x)+(-4x)(+5x²)-(-2x)(-4x)(-3x)+2x(-8x²) =
=+12x³-20x³+24x³-16x³ =0
(-8ab)(-5ab)-(-5a²)(-6b²)+(3a)(-10ab²)=
=+40a²b²-30a²b²-30a²b²=-20a²b²
=+12x³-20x³+24x³-16x³ =0
(-8ab)(-5ab)-(-5a²)(-6b²)+(3a)(-10ab²)=
=+40a²b²-30a²b²-30a²b²=-20a²b²
Alte întrebări interesante
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Informatică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
10 ani în urmă
Matematică,
10 ani în urmă